Effectiveness of Implementation of Police Role in Mediating Indigenous Community Conflicts (Study at Sorong City Police Department) - Panjaitan, Junias Hasintongan; Suwondo, Denny (Jurnal Hukum Khaira Ummah, 2025)
Conflicts in indigenous communities, particularly customary land disputes, present significant challenges due to the coexistence of customary and state legal systems. In this context, the police play a crucial role as mediators to bridge these two legal frameworks and achieve fair and peaceful resolutions. This study aims to examine the effectiveness of police role implementation in mediating indigenous community conflicts at Polresta Sorong Kota. Employing a qualitative approach with data collected through interviews, observations, and document analysis, the study reveals how the police perform mediation functions and the obstacles encountered. Findings show that although the police strive to mediate through dialogue and deliberation approaches while integrating customary and formal laws, significant challenges remain regarding knowledge of customary law, cultural training, and operational guidelines. Enhancing mediation effectiveness can be achieved through officer training and active involvement of customer leaders. Effective mediation positively impacts dispute resolution without violence, maintains social harmony, and improves the sense of justice among indigenous people. The study recommends strengthening officer capacity, establishing clear guidelines, and collaboration with related institutions to support more effective and sustainable mediation of indigenous community conflicts.